In vitro selection of ribozyme ligases that use prebiotically plausible 2-aminoimidazole–activated substrates - Walton, Travis (Proc Natl Acad Sci U S A, 2020)
The hypothesized central role of RNA in the origin of life suggests that RNA propagation predated the advent of complex protein enzymes. A critical step of RNA replication is the template-directed synthesis of a complementary strand. Two experimental approaches have been extensively explored in the pursuit of demonstrating protein-free RNA synthesis: template-directed nonenzymatic RNA polymerization using intrinsically reactive monomers and ribozyme-catalyzed polymerization using more stable substrates such as biological 5′-triphosphates. Despite significant progress in both approaches in recent years, the assembly and copying of functional RNA sequences under prebiotic conditions remains a challenge. Here, we explore an alternative approach to RNA-templated RNA copying that combines ribozyme catalysis with RNA substrates activated with a prebiotically plausible leaving group, 2-aminoimidazole (2AI). We applied in vitro selection to identify ligase ribozymes that catalyze phosphodiester bond formation between a template-bound primer and a phosphor-imidazolide–activated oligomer. Sequencing revealed the progressive enrichment of 10 abundant sequences from a random sequence pool. Ligase activity was detected in all 10 RNA sequences; all required activation of the ligator with 2AI and generated a 3′-5′ phosphodiester bond. We propose that ribozyme catalysis of phosphodiester bond formation using intrinsically reactive RNA substrates, such as imidazolides, could have been an evolutionary step connecting purely nonenzymatic to ribozyme-catalyzed RNA template copying during the origin of life.